KONFLIK BATIN TOKOH MARK: EKSPLORASI DIMENSI PSIKOSOMATIS DENGAN PENDEKATAN FREUDIAN DALAM DINAMIKA KELUARGA M (BLOOMINGTON RESIDENT) - M. Hikmal Yazid (Bahasa Indonesia Prima, 2024)
This study aims to conduct a Freudian psychosomatic analysis of the moral struggle of Mark's character in the short story